Change in physiotherapy students’ attitudes towards cooperation in an interdisciplinary medical team - Gotlib, Joanna; Białoszewsk, Dariusz; Cabak, Anna; Barczyk, Katarzyna; Bauer, Aleksandra; Grzegorczyk, Joanna; Kułak, Wojciech; Majcher, Piotr; Nowotny-Czupryna, lga; Płaszewski, Maciej; Prokopowicz, Katarzyna; Sierdziński, Janusz (Polish Journal of Public Health, 2010)
Introduction. Effective collaboration within a medical team is playing an increasingly important role in ensuring a high level of service in health care. Students of medical degree programs perceive other medicine-related professionals in a predetermined, frequently stereotypical manner from the very beginning of their university education. University education, instead of verifying the image, reinforces it.Aim. The objective of this study was to analyze the participants’ perceptions of cooperation in an interdisciplinary medical team, and to compare the perception of this cooperation among first- and third-year students at medical universities (MS), universities of physical education (PE), and other university-level schools (OU).Material and methods. The study involved 1145 students from 11 Polish university-level schools of different educational orientations. The same students were surveyed voluntarily on two occasions: during their first and third year of studies. The research tool was an anonymous standardised questionnaire designed by the authors (88 questions). The statistical analysis (STATISTICA 9.0) was conducted using the non-parametric chi-square (χ2) test (p